Optimasi Distribusi Produk Pertanian dengan Metode North-West Corner - Praba, Ardian Dwi; Safitri, Maryanah; Faridi, Faridi (Universitas Muhammadiyah Tangerang, 2024)
Optimal distribution of agricultural products is the key to minimizing logistics costs, increasing farmers' profits, and reducing product prices for consumers. This research focuses on optimizing the distribution of agricultural products from several farmers to various markets using the North-West Corner (NWC) method. The NWC method is a heuristic approach that is easy to understand and apply to solve transportation problems with a balanced number of sources and destinations. This research utilizes actual data regarding transportation costs, market needs and product availability from farmers. The research results show that the NWC method is able to produce optimal distribution solutions with minimum transportation costs. The application of the NWC method can help farmers increase profits and increase the efficiency of distribution of agricultural products. This research makes a significant contribution in increasing the efficiency of the agricultural product supply chain, improving farmer welfare, and triggering the accessibility of agricultural products for consumers at more affordable prices.